А.ӘБДИЕВТИҢ «ҚАРАҚАЛПАҚ ҚОСЫҒЫ ЯМАСА НАН ЖЕҢИЗ!» ГҮРРИҢИНДЕГИ КӨРКЕМЛИК ИЗЛЕНИСЛЕР - Ктайбекова, З.К. (SCIENCE and SOCIETY, 2024)
The article analyzes the artistic research in Karakalpak stories. As a research object, the well-known writer A. Abdiev’s "Karakalpak song or taste bread!" the story named. In his work, the author’s unique skill in describing the events, describing the national customs and traditions of our people, using artistic words, proverbs, and aphorisms is highlighted on the basis of examples. The stylistic researches in the use of artistic detail, dialogue highlighting the image of the characters, are analyzed on a scientific and theoretical basis.